KEMUNCULAN ISLAM DI PAKISTAN DAN PEMIKIRAN POLITIK MUHAMMAD ALI JINNAH - Ahmad Dhiyaul Haq Mahsyar; Hasaruddin (Rumah Jurnal STAIN Majene, 2022)
This research uses qualitative research methods with the type of literature study research. The data collection technique uses Library Research and the technique uses to analyze data is text content analysis. Tne emergence of Islam began to spread in Pakistan when the Umayyah Dynasty government expanded into the Sindi/Punjab area led by Mahmud Ghaznawi. As time went on, Hindus did not like the development of Islam. For this reaseon, the Indian Muslim League, which was initiated bu Muhammad Ali Jinnah, serves to establish an Islamic State that is different and free from Indian influence. The most prominent idea of renewal is in political sphere. Ali Jinnah did not like the British system of government. Finnaly, Ali Jinnah’s resolve was discussed in Lahore in 1940. Ali Jinnah has worked to fight for rights for Muslims as there is a third of the Muslim representation that exists in the League’s Federal Cabinet. He also succeeded in establishing the state of Pakistan as a result of his approach to the British constitutional council devoted to Indians who are Muslim.